Effectiveness of Integrated Couples Therapy on Intimacy and Marital Forgiveness among Women Affected by Extramarital Relationships - Salehi, Mohadeseh; Nikoo Abkenar, Bita; Yeganeh Sarajari, Maryam (Psychology of Woman Journal, 2023)
Objective: One of the most significant factors that can disrupt family health is the breakdown of commitment and exclusivity in emotional and sexual relationships and the creation of extramarital relationships, or marital infidelity. The current study aimed to determine the effectiveness of integrated couples therapy on intimacy and marital forgiveness among women affected by marital infidelity.Methods and Materials: This study was a quasi-experimental research with a pre-test, post-test, and three-month follow-up design, including a control group. The study population consisted of all women affected by marital infidelity who sought counseling at Tehran counseling centers in 2023. Among them, 30 participants were selected through purposive sampling and were randomly assigned to either the experimental or control group. Data were collected using the Marital Intimacy Scale (Thompson & Walker, 1988) and the Marital Forgiveness Questionnaire (Rey et al., 2001). The experimental group received Emotion-Focused Therapy over 9 sessions (once a week for 90 minutes each). Data were analyzed using repeated measures ANOVA with SPSS version 22.Findings: Results showed that integrated couples therapy significantly increased forgiveness (F=5.54, P